2022
DOI: 10.1002/ajoc.202200605
|View full text |Cite
|
Sign up to set email alerts
|

Spirobisnaphthalenes from Fungi, Biological activities and Total Synthesis: A Research Review

Abstract: Spirobisnaphthalenes are a family of natural products containing two naphthalenes connected with spiroketal or dinaphthalene spiroether. This family of natural compounds has a wide range of biological activities and complex structures, and has attracted great attention from synthetic chemists in recent years. Hundreds of novel spirobisnaphthalenes have been identified from the first separation in 1989. Despite the slow pace of research in recent years, since the latest review in 2017, 30 new natural products h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…[12] Additionally, here spirobisnaphthalenes were initially discovered inCladosporium , representing a growing family of rare natural products containing two naphthalene-derived C10 units bridged through a spiroketal linkage. [4,21] Furthermore, the summary of UV absorption profiles for cladosporols and spirobisnaphthalenes provides valuable evidence that may encourage further in-depth investigation of these compounds. Collectively, this study explored the metabolites produced by endophytic fungi found in toad skin and their anti-tumor activity, offering valuable insights for gaining a deeper understanding of the symbiotic relationship between animals and their associated fungi, and its potential implications for host health.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Additionally, here spirobisnaphthalenes were initially discovered inCladosporium , representing a growing family of rare natural products containing two naphthalene-derived C10 units bridged through a spiroketal linkage. [4,21] Furthermore, the summary of UV absorption profiles for cladosporols and spirobisnaphthalenes provides valuable evidence that may encourage further in-depth investigation of these compounds. Collectively, this study explored the metabolites produced by endophytic fungi found in toad skin and their anti-tumor activity, offering valuable insights for gaining a deeper understanding of the symbiotic relationship between animals and their associated fungi, and its potential implications for host health.…”
Section: Discussionmentioning
confidence: 99%
“…Spirobisnaphthalene natural products, which were divided into five types based on the different linkages of the two naphthalenes, have a broad biological activities, such as antifungal, antimicrobial, antitumor, anticancer, antiparasitic, anti-inflammatory, and cytotoxic activity. Many reports related to the total synthesis, structure revision, and modification, and biological activity evaluation of the spirobisnaphthalene natural products have appeared in recent years, in which spiromamakone A and its monobenzo analogue (Figure B) showed excellent cytotoxicity against cervical carcinoma HeLa cells with IC 50 value of 0.77 and 0.56 μM, respectively. Some of works have also been carried out in the total synthesis and biological activities of this family of natural products in our group. …”
Section: Introductionmentioning
confidence: 99%